A Rare Case of Lipomatous Variant Mammary-Type Myofibroblastoma of the Lateral Tongue - Matthew Spalti; Firoozeh Samim; Livia Florianova (Case Reports in Dentistry)
Mammary-type myofibroblastoma (MTMF) is an unusual and rare benign tumor that typically presents in older men or post-menopausal females. A 53-year-old female presented with a 6-month history of an asymptomatic pink/white submucosal nodule involving the left lateral tongue. Clinical examination showed a 5 mm×5 mm×5 mm firm submucosal nodule with intact overlying mucosa. Differential diagnoses focused on benign nodular connective tissue tumors. An excisional biopsy was performed and submitted for histopathological examination. The patient underwent conservative local excision. Histopathology and immunocytochemistry revealed a lipomatous variant of MTMF. Hematoxylin and eosin sections revealed an unencapsulated soft tissue lesion with a lobular growth pattern. The neoplasm was biphasic, comprising adipose tissue and cellular fibrous components. By immunohistochemistry, tumor cells were positive for desmin, estrogen receptor, and CD34. In summary, we presented an unusual case of a lipomatous variant of myofibroblastoma on the tongue. MTMF rarely occurs in the head and neck and its accurate diagnosis necessitates awareness of its histomorphological spectrum and application of appropriate immunohistochemical stains.